Enhancing Vocational Digital Marketing Competencies through Project-Based Learning and TikTok Integration in Package C - Putri, Fina Akmalia; Lestari, Gunarti Dwi; Yulianingsih, Wiwin; Ardiyanti, Dwi; Syarifah, Virda (LPPI Yayasan Almahmudi bin Dahlan, 2026)
The purpose of this study was to analyze the implementation of TikTok-integrated Project-Based Learning (PjBL) in improving digital marketing vocational competencies in the Package C equivalency program. A qualitative approach was used with a case study design at PKBM Anggrek Bulan Banyuwangi. Participants involved 25 learners with diverse characteristics, ranging from high school students to housewives with side jobs. Interview informants were selected through purposive sampling, consisting of PKBM heads and learners. Data were collected through observation, semi-structured interviews, and documentation. The results showed that learners were able to understand the basic stages of digital marketing through TikTok, such as affiliate strategies, hashtag use, trending audio, and the preparation of promotional content for local Banyuwangi products, especially golden dragon fruit. Project-based learning also improved content creativity and marketing communication skills of learners.